Media Pop-Up Book Using Adobe After Effect Material on Procedures for Ablution in Kindergarten - Susi, Susi Suhajah; S Sumarni; E Ratna Kartika Wati (Jurnal Edutech Undiksha, 2023)
Media variations in familiarizing ablution procedures for early childhood are still limited to pictures and posters. This problem causes a lack of knowledge in children about the correct sequence of ablution. This study aims to develop pop-up book media using Adobe After Effects, material for ablution procedures for group B children in Kindergarten. The type of research used is development research referring to the ADDIE model. The research subjects comprised one media expert, a material expert, a linguist, and 30 students. Data collection methods used are interviews, questionnaires, and observation. The instrument used is a closed questionnaire. The analysis technique used is descriptive qualitative and quantitative. The results showed good validation consisting of 86% material validation, 100% media, and 88% language. While the practicality of the media is 89%, the category is very good. The effectiveness test results showed that the use of book pop-up media increased children's understanding of the procedures for ablution. It was concluded that pop-up book media using Adobe After Effects is valid, practical, effective, and appropriate to be used as a learning media for kindergarteners' ablution procedures for group B children. Using Adobe After Effect, pop-up book media can increase enthusiasm and make it easier for children to learn how to perform ablution.